Supersaturable Self-nanoemulsifying Drug Delivery System: A Comprehensive Review - Muthadi Radhika Reddy; Kumar Shiva Gubbiyappa (Challenges and Advances in Pharmaceutical Research Vol. 10, 2022)
A better method for improving the solubility and bioavailability of weakly water-soluble chemicals is to use self-nanoemulsifying drug delivery systems (SNEDDS). These formulations do, however, have a few drawbacks, such as drug precipitation in vivo, poor in vitro in vivo correlation because in vitro testing are not available, handling concerns with liquid formulation, and physico-chemical instability of pharmaceuticals. Potential solutions, such as supersaturable SNEDDS (S-SNEDDS), which are generated by adding precipitation inhibitors (PIs) into formulated SNEDDS to preserve drug supersaturation after dispersion in gastrointestinal tract, are able to overcome these constraints. These systems lessen inconsistent exposure and increase medication bioavailability. These formulations also aid in overcoming the limitations of dose forms like liquid and pill. The S-SNEDDS offers a practical method for enhancing the bioavailability and solubility of anti-cancer drugs. This review article explains about SNEDDS, factors affecting supersaturation, the PIs used, mechanism of precipitation inhibition and factors effecting precipitation or drug supersaturation and applications. This article also emphasizes on nanodrugs for treatment of and application of S-SNEDDS in cancer therapy.